To Ultrasound or not to Ultrasound: A REBOA Femoral Access Analysis from the ABOTrauma and AORTA Registries - Duchesne, Juan; McGreevy, David; Nilsson, Kristofer; DuBose, Joseph; Rasmussen, Todd E; Brenner, Megan; Jacome, Tomas; Hörer, Tal; Tatum, Danielle (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is becoming a standardized adjunct in the management of non-compressible hemorrhage. Ultrasound (US)-guided femoral access has been taught as the best practice for femoral artery cannulation. However, there is a lack of evidence to support its use in patients in extremis with severe hemorrhage. We hypothesize that no differences in outcome will exist between US-guided and to blind percutaneous or cutdown access methods. Methods: This was an international, multicenter retrospective review of all patients managed with REBOA from the ABOTrauma Registry and the AORTA database. REBOA characteristics and outcomes were compared among puncture access methods. Significance was set at P < 0.05. Results: The cohort included 523 patients, primarily male (74%), blunt injured (77%), with median age 40 (27–58), and an Injury Severity Score of 34 (25–45). Percutaneous using external landmarks/palpation was the most common femoral puncture method (53%) used followed by US-guided (27.9%). There was no significant difference in overall complication rates (37.4% vs 34.9%; P = 0.615) or mortality (47.8% vs 50.3%; P = 0.599) between percutaneous and US-guided methods; however, access by cutdown was significantly associated with emergency department (ED) mortality (P = 0.004), 24 hour mortality (P = 0.002), and in-hospital mortality (P = 0.007). Conclusions: In patients with severe hemorrhage in need of REBOA placement, the percutaneous approach using anatomic landmarks and palpation, when compared with US-guided femoral access, was used more frequently without an increase in complications, access attempts, or mortality.